2011
DOI: 10.1002/path.2850
|View full text |Cite
|
Sign up to set email alerts
|

P‐selectin glycoprotein ligand‐1 modulates immune inflammatory responses in the enteric lamina propria

Abstract: P-selectin glycoprotein ligand-1 (PSGL-1), a leukocyte adhesion receptor that interacts with selectins, induces a tolerogenic programme in bone marrow-derived dendritic cells (DCs), which in turn promotes the generation of T regulatory (Treg) lymphocytes. In the present study, we have used a mouse model of dextran sulphate sodium (DSS)-induced colitis and studied the characteristics of the inflammatory cell infiltrate in the lamina propria (LP), mesenteric lymph nodes (mLNs) and Peyer's patches (PPs) to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…There is also evidence that engagement of PSGL-1 by P-selectin or E-selectin can trigger proliferative and differentiation signals in hematopoietic cells, including hematopoietic progenitors 88 and dendritic cells, 89 with functional consequences during inflammation. 90 The signaling pathways controlling these processes have not been described.…”
Section: Selectin Ligand-mediated Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that engagement of PSGL-1 by P-selectin or E-selectin can trigger proliferative and differentiation signals in hematopoietic cells, including hematopoietic progenitors 88 and dendritic cells, 89 with functional consequences during inflammation. 90 The signaling pathways controlling these processes have not been described.…”
Section: Selectin Ligand-mediated Signalingmentioning
confidence: 99%
“…There is also evidence that engagement of PSGL-1 by P-selectin or E-selectin can trigger proliferative and differentiation signals in hematopoietic cells, including hematopoietic progenitors 88 and dendritic cells, 89 with functional consequences during inflammation. 90 The signaling pathways controlling these processes have not been described.Little is known about the possible pathophysiologic roles of ESL-1, but a potential contribution to vascular occlusion in sickle cell disease has been recently described. 85 In a murine model of sickle cell disease after challenge with tumor necrosis factor-␣, interactions between sickle-shaped erythrocytes and neutrophils generate intravascular cell aggregates that trigger the vasoocclusive episodes characteristic of patients with this disease.…”
mentioning
confidence: 99%
“…The administration of anti-PSGL-1 antibodies in mice reduced the total number of macrophages, dendritic cells, and B lymphocytes in the lamina propria, and decreased the expression of MHC-II on dendritic cells and macrophages (25).…”
Section: Discussionmentioning
confidence: 95%
“…Autoantibodies (mainly anti-Ro-SS-A and anti-La-SS-B) contribute to playing roles in its clinical pictures (2). Central and peripheral nervous system involvement may be seen as different sign, symptoms and varying its frequencies (2). Objectives: The aim of this study is to investigate the frequency of neurological and other involvement patterns of the Sjögren's syndrome (SjS).…”
Section: Ab0127 the Frequency Of Nuerological Involvement Inmentioning
confidence: 99%
“…Plasmacytoid DCs (pDCs) are potent type I interferon (IFN) producers and myeloid DCs (mDCs) are professional antigen-presenting cells. Clinically, the level of serum interferon alpha (IFNa) correlates with the severity of disease with pDC infiltration in nephritic kidney suggested that pDCs may contribute to SLE pathogenesis [1,2]. Moreover, monocyte-derived mDCs from SLE patients also display activated phenotypes [3].…”
mentioning
confidence: 99%